Exploring Insecure Romantic Attachment and Justifications for the Use of Intimate Partner Psychological Aggression in Couples - Leclerc, Marie-Eve (Journal of interpersonal violence, 2022)
The attachment theory has commonly been used to examine intimate partner psychological aggression (IPPA), but few studies have examined its association with self-reported justifications for one?s own use of IPPA. Behaviors, including the use of IPPA, are influenced, maintained, and function within the context of their justifications, highlighting the importance of investigating these justifications to obtain a clearer picture of IPPA. This study examined whether insecure romantic attachment (i.e., attachment anxiety and attachment avoidance) in both partners of a couple was associated with their justifications for their own use of IPPA. A community sample of 81 mixed-sex couples who reported using IPPA in the last year completed self-reported questionnaires on adult romantic attachment and their justifications for their use of IPPA. Results of a path analysis based on the actor-partner interdependence model revealed moderate positive associations between attachment anxiety and one?s use of internal and external justifications for their IPPA perpetration in men and women. An unexpected dyadic positive association is discussed. These results suggest that the use of justifications for one?s use of IPPA may reflect a strategy of hyperactivation that could contribute to the cycle of psychological aggression. Uncovering the function of these justifications could provide important therapeutic benefits, which are discussed in the study?s implications.